Ensaios sobre o programa de parentalidade “pais e cuidadores são construtores de cérebros” - Corrêa, Camila Guedes (2023)
Early childhood is a large window of opportunities for the formation of qualified human capital, so the incentives for children to fully develop their skills must exist in the family and social environment. Observing this, the present study carries out two tests on the Parents and Caregivers are Brain Builders program. The first presents an exploratory and descriptive analysis, through the construction of the Logical Framework and Theory of Change of the program that proposes the promotion of positive parenting among parents and caregivers in situations of economic vulnerability and at social risk, for child development with a focus in the language of Brazilian children aged 0 to 5 years. Evidence suggests that the actions and activities adopted by the program are capable of encouraging caregivers to adopt responsive interactions with their children through verbal and non-verbal language, aiming at bond formation and language development in early childhood. In the second trial, with the interest of analyzing whether participation causes effects on the opinions and perceptions of caregivers, a qualitative evaluation was carried out, using the focus group technique, of the caregivers' speeches in a period before and after participation in the group. parents and caregivers. When using Iramuteq, the parents' speech verifies the important terms and concepts that are presented throughout the 11 sessions discussed with the caregivers. More than that, it was observed that those responsible who participated in the sessions became more specific when answering the questions, discussing how to support child development at home and the acquisition of children's linguistic and cognitive skills.